THE EFFECT OF A COMBINATION OF MORINGA LEAF PUDDING AND HONEY ON HEMOGLOBIN LEVELS IN FEMALE ADOLESCENTS AT SMK IBRAHIMY 1 SUKOREJO - Neny Yuli Susanti; Ifa Nurhasanah; Siti Nurhidayati; ⁠Lia Fitria; Nur Rahmawati Sholehah; ⁠⁠Ika Wijayanti; Miftakhur Rohmah; Jasmiati (PROFESSIONAL HEALTH JOURNAL, 2026)
Background: Iron-deficiency anemia is one of the health issues commonly experienced by adolescent girls, which can affect academic concentration, physical endurance, and quality of life. Natural ingredients such as moringa leaves and honey contain iron and other supportive nutrients that have the potential to be used as non-pharmacological alternatives to increase hemoglobin levels. Objective: This study aims. to investigate the impact of administering a combination of moringa leaf pudding and honey on the hemoglobin. levels of adolescent girls. Methods: This research used a quantitative method with a quasi-experimental design and a non-equivalent control group strategy. A total of 60 female students in grade eleven participated, split into an intervention group and a control group. The intervention group was given moringa leaf and honey pudding once per day over a period of seven days. Hemoglobin levels were assessed before and after the intervention using a digital hemoglobin meter. The data .were evaluated using the Wilcoxon and. Mann-Whitney statistical tests. Results: The average hemoglobin level in the intervention group rose from 10.19 g/dL to 13.57 g/dL, which was statistically significant (p < 0.05). In contrast, the control group showed no significant change, with levels remaining virtually the same at 11.68 g/dL to 11.67 g/dL (p > 0.05). The Mann-Whitney. test indicated a significant difference .between the two groups (p = 0.000). Conclusion: The combination of moringa leaf pudding and honey significantly increased. hemoglobin levels in adolescent girls. This intervention has the potential to become an alternative strategy for preventing anemia among adolescents.